Messaging application / Yew Hooi Phaik - Yew, Hooi Phaik (2001)
Statistics have shown that more and more people are switching to WAP (Wireless Application Protocol) handphones and most people would have heard of WAP before. Undeniably WAP's future is bright and WAP applications prospects are even better. This alone has encouragrd many programmers into developing WAP applications. Study had shown that this is true in part of the world with more and more hooking up to WAP hand phones. Internet Messaging programs have existed for a long time. Currently there's no WAP Messaging Application (WAP-MA) but it's just a matter of time before somebody invented it. This project is involved in developing a WAP Messaging Application. It would be a simplified messaging program compared to other more complicated internet messaging programs because WAP's limitations also constrain WAP-MA to have many functions. The system is developed in Windows NT platform integrating Apache Web Server, Oracle 8i and a SMTP Mail Server. Java Server Pages (JSP) and Wireless MarkUp Language (WML) are the two main programming languages used as the development technology. The development software used in testing the system is Nokia WAP Toolkit which is an emulator by Nokia to enable W AP programs to be tested out on computer.